Random laser speckle pattern projection for non-contact vibration measurements using a single high-speed camera. (September 2021) - Etchepareborda, Pablo; Moulet, Marie-Hélène; Melon, Manuel
Graphical abstract: Highlights: Noncontact vibration measurement with high-speed camera and laser speckle projector. This structured light system allows measuring objects without noticeable features. Protocol successfully applied to measure flat and bent plates with varied surfaces. Abstract: 3D vision methods are a powerful tool for measuring full-field vibration patterns in the most varied types of surfaces. Digital Image Correlation is typically used to track noticeable features on the surface in order to measure local displacements on the tested system. In this work, a novel randomly structured light system based on laser speckle pattern projection and its calibration procedure are proposed for applying computer vision methods to the measurement of vibration in featureless or reflective objects without modifying them. A simple projector is used based on a laser beam affected by a diffuser element. A stereovision set-up with at least one high-speed camera is used to record video sequences from which the initial shape and evolution of the sample displacement are obtained. The vibration mode behavior of different steel plates are obtained using this full-field vibration measuring technique. The pros and cons of the proposed method are discussed and compared to similar stereovision set-ups.